Pride and prejudice: Why science is sexist - Gaston, Nicola (New Zealand Science Review, 2014)
​It is a truth universally acknowledged, that a man in possession of a white coat and a bad haircut is more likely than any woman to be a scientist.‘Science remains institutionally sexist’. This is the claim with which Nature addressed the matter of women in science, in an issue dedicated to the subject in 2013. The sexism referred to is evident in the lower representation of women in the scientific workforce – an imbalance made dramatically clear by the low number of female Nobel Laureates (fewer than 2% of the Chemistry and Physics Laureates to date), or Fellows of the Royal Society of New Zealand (9%), or their overseas equivalents. More pragmatically, women have lower success rates for research grants and have lower citation rates. There is therefore no question whether science is sexist: it is however of considerable importance to understand why this is the case – assuming, of course, that we would like to understand how to fix the current situation.